(untitled) (Journal of the College of Education for Women, 2019)
Baghdad Lake Touristic is suffering from a lake of tourism and entertainment servicesefficiency provided to their visitors , knowing that this type of services as they are the basicsto achieve economic and socialist development because of their indicators where their goal isto serve human in city as they represent lungs which population breathe within .The Parks are resorted as human usually in search of quiet and funny places , away fromthe noise of the city and its complex , as well as they give the city a beauty manifestations ,that give happiness.The study reached that there is deficiencies in service present, inability to provideservices and inadequate for the population and bad distribution. So the study gives a set ofsolutions to heal these deficiencies in tourism and recreational development.